The Influence of Supply Chain Capabilities, Digital Twins, Supply Chain Resilience, and Supply Chain Performance on Supply Chain Sustainability in the National Oil and Gas Industry - Sujendi, Sindi Kharisyani; Siagian, Yolanda Masnita (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
The implementation of digital twins increases integration at every level of work, improves skills, and work culture, and forms a digital culture. Digital twins support real-time monitoring of ship movements, rapid decision-making in predictive maintenance, and identification of abnormalities in the early stages, which improves maintenance, production reliability, and information integration. It also simplifies supply chain procedures, reduces disruptions, and improves adaptation to change and the sustainability of the supply chain business. This study analyzes the effect of Supply Chain Capabilities, Digital Twins, Supply Chain Resilience, and Supply Chain Performance on Supply Chain Sustainability in the national oil and gas industry. Primary data were obtained through questionnaires distributed to 328 employees in the Pertamina supply chain sector, covering various functions such as exploration, production, service, marketing, distribution, and processing. The analysis method used is Structural Equation Modeling with the Analysis Moment of Structure program. The results of the study indicate that Supply Chain Capabilities and Digital Twins have a positive and significant effect on Supply Chain Resilience and Supply Chain Performance, and both have a positive effect on Supply Chain Sustainability.